Exploring Program Directors’ and Faculty’s Perception and Factors Leading to Burnout in Higher Education Institutions in Azerbaijan - Imanguliyeva, Gunay (ADA University, 2020)
Burnout, which may have negative effects on employees’ well-being and the quality of work, is one of the concerning issues in education. The present paper aimed to explore the concept of burnout among program directors and faculty working in three higher education institutions (HEIs) in Azerbaijan. The researcher intended to explore how program directors and faculty working in HEIs perceived the concept of burnout and identify the factors contributing to burnout and the possible consequences of this syndrome on research participants’ professional and personal life. The researcher believed that if the concept of burnout was defined precisely and explored among more faculty, administration, and educational institutions, university leadership may have looked for the ways to support program directors and faculty, which would increase job satisfaction and decrease turnover. An exploratory qualitative research design was chosen for this study. The conceptual framework of this study was based on the Maslach Burnout Inventory. The instruments of the research were semi-structured interviews, observation, and document review. Three EFL (Teaching English as a Foreign Language) instructors and three program directors of the English Language Department working in three higher educational institutions in Azerbaijan participated in this study. The major findings of this study showed that both program directors and faculty suffered from burnout. Though they were aware of the factors that caused burnout, they did not know how to deal with this feeling. While research participants had a high feeling of Emotional Exhaustion and Depersonalization, they had a low feeling of Personal Accomplishment. This research provided a foundation for the concept of burnout in higher educational institutions in Azerbaijan. The researcher suggests that further research is important to measure the level of burnout and to enable HEIs to increase the productivity of program directors’ and faculty’s work as well as decrease the rate of retention in future. Also, in order to help program directors and faculty to cope with burnout, the research recommends the university leadership to meet their psycho-social needs, emotional-physical needs, and personal-intellectual needs.
Keywords: Education; Education, Higher -- Azerbaijan.; Education, Higher -- Burnout -- Azerbaijan.